Strategic Synthesis of Hierarchical Co3O4/ZSM-5 Zeolite as A Catalyst in Partial Oxidation of Methane: Bottom-up vs Top-down Methods - Khatrin, Irena; Putri, Danika Nurranalya; Ridwan, Muhammad; Krisnandi, Yuni Krisyuningsih (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Methane, a potent greenhouse gas contributing approximately 19% to global warming and possessing a global warming potential 28 times greater than carbon dioxide, necessitates conversion into more beneficial chemicals. Partial oxidation of methane to methanol is a promising conversion method which is both time- and cost-efficient. This study synthesized ZSM-5 using two strategic syntheses: Bottom-Up and Top-Down, followed by cobalt oxide impregnation at varying percentages 2.5, 5, and 10% (w/w) to produce Co3O4/ZSM-5. To investigate its physicochemical properties, ZSM-5 catalysts were thoroughly characterized with XRD, FTIR, XRF, N2-physisorption, and SEM. These catalysts were then evaluated in methane partial oxidation reactions conducted in a batch reactor, with a CH4:N2 feed ratio of 0.75 bar:2 bar, at 150 °C for 60 minutes. Co3O4-supported Bottom-Up ZSM-5 with 5% Co-loading demonstrated the largest percentage yield of 62.08% compared to the other Co-loading amount and ZSM-5 synthesized via Top-Down method. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).